Akselerasi Pertumbuhan Bank Syariah di Indonesia - Muhammad Kamal Zubair (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
This paper aims to show the growth of Islamic banking industry in Indonesia. In this time, fast growth of Islamic banking industry progressively is office network side as consequence of improvement of requirement of society and enthusiasm of bank to provide service. Bank of Indonesia estimate in the this year 2008, Islamic banking industry will enjoy high growth to be compared to national banking in general. This prediction based on the finishing Law of Islamic Securities (SBSN) and Law of Islamic Bank (UUPS) and completion of Law TaxationKeywords: bank syariah, pertumbuhan, bank Indonesia